Studi in silico Molecular Docking Senyawa Bioaktif Tumbuhan Pelawan (Tristaniopsis merguensis Griff) sebagai Kandidat Inhibitor α-Glukosidase untuk Antidiabetes - Mesi Anggun Sari; Trisna Kumala Sari (Lembaga Yasin AlSys, 2026)
Diabetes mellitus is a metabolic disease with a continuously increasing prevalence and may be influenced by dietary patterns, diet, physical activity, and age. One strategy for controlling it is to inhibit the activity of the α-glucosidase enzyme, which plays a role in breaking down carbohydrates into glucose. Pelawan (Tristaniopsis merguensis Griff.) contains bioactive compounds, such as flavonoids, terpenoids, saponins, and phenols, that have the potential to be developed as antidiabetic agents. This study aimed to evaluate the potential of bioactive compounds from pelawan to inhibit the activity of the α-glucosidase enzyme (PDB ID: 1LHU) through an in silico approach. Molecular docking simulations were performed using PyRx and PyMOL software, while protein–ligand interactions were visualized using Discovery Studio 2025. The results showed that kaempferol had the best binding affinity, with a value of −8.1 kcal/mol, followed by resveratrol, with a value of −7.3 kcal/mol. The visualization results showed interactions between the protein and ligands through hydrogen bonds as well as hydrophobic and alkyl interactions. These findings indicate that kaempferol and resveratrol from T. merguensis have the potential to inhibit α-glucosidase activity. This study supports the potential of bioactive compounds from pelawan as natural antidiabetic candidates and provides a basis for further research to validate their biological activity.